1988
DOI: 10.1111/j.1464-0597.1988.tb01147.x
|View full text |Cite
|
Sign up to set email alerts
|

Self‐assessment in Personnel Selection: An Investigation Using Seasonal Workers

Abstract: Il existe une controverse sur la valeur de l'autoévaluation dans la sélection professionnelle. Peu d‘études appliquées sont actuellement disponibles. Cette recherche s'intéresse à l'amélioration que l'autoévaluation procure à la validité prédictive des actuelles procédures de sélection. On a pris en considération diverses variables susceptibles d'intervenir (le sexe, l’âge, l'expérience professionnelle, l'information sur l'emploi, le niveau culturel, l'expérience de l'autoévaluation et les jugements absolus ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

1995
1995
2004
2004

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 39 publications
1
6
0
Order By: Relevance
“…In this latter instance candidates may have been intent on presenting favourable evidence and based their judgements on predominantly positive behaviours rather than a more balanced sample, resulting in lower congruence with referees. Social comparison instructions had no impact on the validity of self-ratings, consistent with findings reported by George and Smith (1988) for SAs collected at assessment centres. This suggests instructions containing reference to others may elicit a different response in selection than in other settings where improvements are often found (Heneman, 1986;Mabe & West, 1982).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In this latter instance candidates may have been intent on presenting favourable evidence and based their judgements on predominantly positive behaviours rather than a more balanced sample, resulting in lower congruence with referees. Social comparison instructions had no impact on the validity of self-ratings, consistent with findings reported by George and Smith (1988) for SAs collected at assessment centres. This suggests instructions containing reference to others may elicit a different response in selection than in other settings where improvements are often found (Heneman, 1986;Mabe & West, 1982).…”
Section: Discussionsupporting
confidence: 86%
“…Festinger (1954) proposed that individuals compare themselves to others in the absence of relevant objective criteria. Some studies have reported that the quality of SAs is improved when instructions are framed in relative terms (Farh & Dobbins, 1989;Mabe & West, 1982), whereas others have found no difference in a selection setting (George & Smith, 1988). No specific predictions are made in view of previously conflicting findings.…”
Section: Lee Jones and Clive Fletchermentioning
confidence: 96%
“…Leniency is generally found when self-ratings are made for the purpose of selection (Anderson et al, 1984;Fox & Dinur, 1988;George & Smith, 1988). It seems likely that individuals may be highly motivated to present themselves favourably if they perceive that their ratings may be linked to valued outcomes as in this context.…”
mentioning
confidence: 99%
“…The other items consisted of comparative judgements of past behaviour and anticipated future behaviour with respect to a range of reference groups. The use of comparative items has been found to yield similar results to absolute items (George and Smith 1988).…”
Section: Instrumentsmentioning
confidence: 99%